The Exocyst Complex in Health and Disease - Martin-Urdiroz, Magdalena; Deeks, Michael J.; Horton, Connor G.; Dawe, Helen R.; Jourdain, Isabelle (Frontiers in Cell and Developmental Biology, 2016)
Exocytosis involves the fusion of intracellular secretory vesicles with the PM, thereby delivering integral membrane proteins to the cell surface and releasing material into the extracellular space. Importantly, exocytosis also provides a source of lipid moieties for membrane extension. The tethering of the secretory vesicle before docking and fusion with the PM is mediated by the exocyst complex, an evolutionary conserved octameric complex of proteins. Recent findings indicate that the exocyst complex also takes part in other intra-cellular processes besides secretion. These various functions seem to converge towards defining a direction of membrane growth in a range of systems from fungi to plants and from neurons to cilia. In this review we summarise the current knowledge of exocyst function in cell polarity, signalling and cell-cell communication and discuss implications for plant and animal health and disease.